2002
DOI: 10.1006/nimg.2002.1117
|View full text |Cite
|
Sign up to set email alerts
|

Imaging the Intentional Stance in a Competitive Game

Abstract: The "intentional stance" is the disposition to treat an entity as a rational agent, possessing particular beliefs, desires, and intentions, in order to interpret and predict it's behavior. The intentional stance is a component of a broader social cognitive function, mentalizing. Here we report a study that investigates the neural substrates of "on-line" mentalizing, using PET, by asking volunteers to second-guess an opponent. In order to identify brain activity specifically associated with adoption of an inten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

21
414
0
6

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 502 publications
(441 citation statements)
references
References 39 publications
21
414
0
6
Order By: Relevance
“…Many of neuroimaging studies on experimental games have found that social interactions with human players produce stronger activations in several brain areas, often in the anterior paracingulate cortex (Fig 3c), than similar interactions with computer players [84][85][86] . Assuming that more sophisticated inferences are used to deal with human players than with computer players, such findings might provide some clues on the cortical areas specialized for theory of mind.…”
Section: Neural Correlates Of Social Decision Makingmentioning
confidence: 99%
“…Many of neuroimaging studies on experimental games have found that social interactions with human players produce stronger activations in several brain areas, often in the anterior paracingulate cortex (Fig 3c), than similar interactions with computer players [84][85][86] . Assuming that more sophisticated inferences are used to deal with human players than with computer players, such findings might provide some clues on the cortical areas specialized for theory of mind.…”
Section: Neural Correlates Of Social Decision Makingmentioning
confidence: 99%
“…Schilbach et al, 2010;Redcay et al, 2012), and play games against a human as opposed to a computer (e.g. McCabe et al, 2001;Gallagher et al, 2002;Coricelli and Nagel, 2009). Such studies, however, often involve either explicit mentalizing, as during strategy games, or do not directly compare stimuli that differ solely on interactive context.…”
Section: Introductionmentioning
confidence: 99%
“…A number of neuroimaging studies have explored ToM in adults and implicated the mPFC as being important for ToM processing (Brunet, Sarfati, Hardy-Baylé, & Decety, 2000;Fletcher et al, 1995;Gallagher et al, 2000;Gallagher, Jack, Roepstorff, & Frith, 2002;Goel, Grafman, Sadato, & Hallett, 1995;Happé et al, 1996;Vogeley et al, 2001). There has been some evidence for modality-dependent ToM processing in laterality effects seen in ToM-related brain activity.…”
Section: Introductionmentioning
confidence: 99%